Various Learning Models to Improve Students' Mathematical Literacy Skills - Fransisca Tanjung Dian Pramesti (EduMa: Mathematics education learning and teaching, 2025)
Mathematical literacy is the ability to understand, formulate, and apply mathematical concepts in everyday life, particularly in solving real-world problems. Key indicators include mathematical thinking, problem-solving, communication, representation, argumentation, and the use of media or technology. This study explores learning models that enhance students’ mathematical literacy through a literature review. The findings show that models such as Problem-Based Learning (PBL), guided inquiry, and Project-Based Learning (PjBL) are effective. These models, which emphasize real-world problems, independent exploration, and student collaboration, help develop critical and creative thinking and strengthen the connection between mathematics and daily life.